Greatest Income Strategy Through Empowerment of Informal Sector Women Entrepreneurs Based on Jambi Malay Culture with the Sustainable Livelihood Framework Approach - Mayasari, Mayasari; Syuhada, Siti; Muslim, Fachruddiansyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines the development of an effective income-maximization strategy by empowering informal sector women entrepreneurs in Jambi, Indonesia, through the Sustainable Livelihood Framework (SLF) approach. It addresses critical challenges including limited access to economic resources, socio-cultural constraints, and policy gaps that hinder women's full participation in entrepreneurship. The research explores the intersection of Jambi Malay cultural values with livelihood assets and empowerment initiatives to enhance women's income generation. Employing a qualitative methodology with a case study approach, the research utilizes in-depth interviews, participatory observation, and document analysis. The findings demonstrate that SLF serves as a valuable analytical tool for understanding the interplay of social capital, human capital, and cultural ethics in income generation. Key determinants of success include access to capital, culturally embedded business practices, product innovation, and strong social networks. However, barriers such as technological illiteracy and inadequate financial infrastructure persist. This study contributes to the discourse on women's economic empowerment by showcasing how culturally embedded frameworks can enhance resilience and optimize income generation. It offers strategic insights for policymakers, practitioners, and stakeholders to develop inclusive and sustainable empowerment programs tailored to local contexts.